Chloride and Sulphate Removal by Using N-GET System with Additional Filters. Issue 1 (May 2021) - Musa, S; Kadir, M N Abdul; Zakaria, N A; Lau, T L
Abstract: Groundwater is an alternative source of water for human consumption. Groundwater at Research Centre of Soft Soil (RECESS), Universiti Tun Hussein Onn Malaysia (UTHM) is one of the water sources that available to be used. Unfortunately, it has a high content of chloride and sulphate concentration in which originated from the mineral content in the ground. This research was conducted to identify the effectiveness of the Nature Groundwater Eco-Treatment (N-GET) system that has been designed at RECESS in removing sulphate and chloride concentration as well as pH and turbidity parameter. N-GET system is a natural treatment process without mixing any substances intended to improve the quality of groundwater can give benefits to users. N-GET system in this study uses two treatment tanks in the treatment of groundwater which are aeration tanks, sedimentation tanks, and three sets of filters which were activated carbon filter, Do-It-Yourself (DIY) filter, and ceramic filter. The chloride and sulphate parameters were tested with 12 numbers of the sample while pH and turbidity were tested with 63 numbers of the sample. Using combination with sedimentation and aeration, ceramic filtration were performing better by reducing the pH of the samples by 3.9% towards neutrality and removed 32.6 % of sulphate, 13.1 % turbidity, and 33.0 % of chloride concentration from RECESS groundwater in comparison to an activated carbon filter, Do-It-Yourself (DIY) filter. Then, the effectiveness of each filter based on design flow and types of particle size in the filter. Therefore, the capability of each filter able to remove the specific contaminant as designed need.